EDUKASI KESEHATAN MENGENAI HIPERTENSI MELALUI PROGRAM SEHAT ITU PENTING (SIP) DI DESA TEMON - Avisya As Zahro; Zaenul Wafa; Ayu Dheemi Dahlan; Dini Hesti Pramita; Yunika Putri Adilia; Qori Martha Ningrum (LPPM AN Nuur, 2024)
Background: Health Education Activity on Hypertension through the Healthy is important called (SIP) Program. This activity is an effort to provide health education to the community, focusing on the dissemination of information on hypertension and health checks. Purpose: The goal of this activity is to increase public awareness about hypertension and the importance of maintaining health. Method: The methods used in this activity include blood pressure measurement, hypertension education, and the development of follow-up plans. Results: The Health Education Activity on Hypertension through the Health is important (SIP) Program cover the evaluation of community health conditions and preventive measures that can be taken to improve health. Conclusion: The Health Education Activity on Hypertension through the Health is Important (SIP). The activity is called (SIP) Program will increase public awareness of the importance of maintaining health and adopting a healthy lifestyle.